Juridical Implications on the Implementation of Marriages What is not Recorded at the Office of Religious Affairs in the Conception of Legal Certainty - Gultom, Maria Yosephine; Tri Bawono, Bambang (Law Development Journal, 2024)
Sirri marriages, which are often not registered under Indonesian positive law, create legal complexities that have the potential to harm the rights of the individuals involved, especially children. Even though in Islamic teachings, this kind of marriage is considered legal, Indonesia's positive legal perspective views it differently. This gives rise to a number of problems that threaten children's welfare, such as the lack of legal certainty regarding marital status, maintenance rights and inheritance rights. At the national legal level, Law No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage and regulations related to children's rights, such as Law No. 39 of 1999 concerning Human Rights, emphasize the importance of the protection and welfare of children. This research aims to identify and analyze the legal implications of unregistered marriages on the rights of the individuals involved, especially the rights of children. The focus of the research will be on legal certainty regarding marital status, maintenance rights and inheritance rights for children born from unregistered marriages. This research takes a normative juridical approach to examine positive criminal law regulations related to the criminalization of unregistered marriages, with a focus on the protection of wives and children. Using a legislative approach and a comparative approach, this research compares the legal rules of other countries to fill in legal ambiguities. Primary legal materials based on the 1945 Constitution of the Republic of Indonesia, the Criminal Code, and other related laws. Data collection methods include literature studies, documents and limited interviews to gain a deeper understanding. Data analysis was carried out using qualitative methods to produce a comprehensive understanding of the phenomenon studied. This research aims to contribute ideas and solutions that can be used in the context of positive criminal law regarding unregistered marriages to prevent harm to the family. The absence of marriage registration can also result in children born from the marriage experiencing difficulties in obtaining their legal rights. For example, the right to inheritance or the right to receive social assistance provided by the government. Without official proof in the form of a marriage record, these children may have difficulty proving their familial relationship with their parents. This can lead to injustice and difficulties in obtaining the rights they should get as Indonesian citizens. Thus, marriages that are not registered at the religious affairs office can have serious consequences for legal certainty, protection of individual rights, and family welfare as a whole. overall. Therefore, it is important for every married couple to ensure that their marriage is officially registered at the authorized office in accordance with the legal provisions in force in Indonesia.